Posidonia oceanica ... - Mecca, Silvia; Casoli, Edoardo; Ardizzone, Giandomenico; Gambi, Maria Cristina (Zenodo, 2020)
Phenology of Posidonia oceanica The Posidonia oceanica shoot density showed higher values for both the Vullatura (mean ± SD: Vu3 = 866 ± 148 shoots/m 2; Vu6 = 619 ± 106 shoots/m 2) and Castello Aragonese (N3 = 667 ± 155 shoots/m 2) acidified stations (Fig. 2a) than that at the control site (NC = 391 ± 95 shoots/m 2). These differences were significant by ANOVA (F = 64.70, p -value <0.001); Tukey’s HSD test reported significantly different p -values between the control and acidified stations (NC –N3: p adj <0.001, NC– Vu3: p adj <0.001, and NC–Vu6: p adj <0.001), and between N3–Vu6 (p adj = 0.03). Comparisons between N3–Vu3 and Vu3–Vu6 did not display significant differences. The number of leaves (adult, intermediate, and juveniles pooled together) significantly varied among months, with the same pattern in both the acidified and control stations (Fig 2b). Maximum values were reported in October and December, whereas the minimum values were found during the summer months (June and August). The ... : Published as part of Mecca, Silvia, Casoli, Edoardo, Ardizzone, Giandomenico & Gambi, Maria Cristina, 2020, Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract, pp. 70-83 in Mediterranean Marine Science 21 (1) on pages 73-75, DOI: 10.12681/mms.20795, http://zenodo.org/record/12551640 ...